Design and open services of JiuTian intelligent network simulation platform - Lei ZHAO; Miaomiao ZHANG; Guangyu LI; Zhuowen GUAN; Sijia LIU; Zhaobin XIAO; Yuting CAO; Zhe LYU; Yanping LIANG (Dianxin kexue)
The JiuTian intelligent network simulation platform was proposed, which could provide wireless communication simulation data services for the open innovation platform.The platform contained a series of scalable simulator functionalities, offering open services that enable users to use reinforcement learning algorithms for model training and inference based on simulation environments and data.Additionally, it allowed users to address optimization tasks in different scenarios by uploading and updating parameter configurations.The platform and its open services were primarily introduced from the perspectives of background, overall architecture, simulator, business scenarios, and future directions.